Simulation of Regulated Power Supply for Solar Photo-Voltaic Model - AL-Duliamy, Mushtaq N. Ahmad; Hojabri, Mojgan; Hamdan, Daniyal; Humada, Ali Mahmood (IJESRT, 2013)
This paper presents the simulation of regulated DC voltage source. The DC source main supply is solar PV model which produce unstable output voltage. The model is done such that the input parameters are the light and the temperature and the output is the unstable voltage. The output current is important parameter to achieve accurate output voltage, that current is measured and fed to the input of the model to be used for equation evaluation. Voltage regulation is needed to make the generated voltage usable. A simple buck converter with PID controller used to regulate the output voltage. SIMULINK is used to simulate the overall system. Simulation result is given to verify the operation of the model.